Masked Hypertension in Adolescents with Type 1 Diabetes Mellitus: An Exploratory Study - Bachar Afandi; Bassam Bernieh; Sana Roubi; Juma Al Kaabi (Dubai Diabetes and Endocrinology Journal)
Introduction: Masked hypertension (MHTN) is the finding of elevated out-of-office blood pressure (BP) measurement. This is a pilot study to evaluate the prevalence of MHTN in adolescents with type 1 diabetes mellitus (T1DM). Patients and Methods: Normotensive, adolescents with T1DM were recruited from Tawam Adolescents Diabetes Clinic at Tawam hospital, Al Ain, UAE. They consented to wear the ambulatory BP monitoring (ABPM) device. The heart rate and ambulatory BP were recorded at 15-min intervals for 24 h. Abnormal systolic BP (SBP) and diastolic BP (DBP) were defined as readings above 135 and 85 mm Hg; respectively. Results: Thirteen patients (10 females) were recruited from “Tawam Adolescents Diabetes Clinic.” The median age was 17 (15–19) years, median BMI 21.4 (14.8–29), and median diabetes duration 9 (3–12) years. All patients had normal retinal examination within the past 12 months. Family history of hypertension (HTN) was present in 6/13 (46%) patients. Office BP measurements revealed a mean DBP ± SD of 72 ± 6.9 mm Hg and mean SBP ± SD116 ± 5.5 mm Hg. The median HbA1c was 8.4% (5.6–13.7) and median GFR 125 mL/min/m2 (87–134). Two patients had microalbuminuria. Twenty-four hour ABPM revealed elevated SBP and DBP in 12.2 and 5.8% of the values; respectively. Further analysis confirmed MHTN in 4 (30%) patients, nondipping pattern of BP in 5 (38%) patients, and elevated pulse pressure in 8 (61.5%) patients. Only 4 (30%) patients had normal studies. Conclusions: ABPM uncovered a very high prevalence of MHTN in our patients. Whenever available, ABPM provides an excellent tool for diagnosis and hence early evaluation and management of HTN in adolescents with T1DM. Well-designed large-scale studies are needed to examine the magnitude of MHTN among adolescents with T1DM.